Plan de mejoramiento enfocado en los procesos para la empresa Soluciones Integrales de Negocios S.A.S ubicada en Armenia Quindío. (2013)
This project aims to improve the processes of a foreign trading company, with the goal of implementing a management and security standard issued by the WBO and make sure their administrative and operational processes, for which is required to make aninternal and external analysis of the organization, make the formulation of strategies, and finally design a proposal for an action plan to comply with the requirements stated above. About the theoretical support, there are two models: the strategic management and continuous improvement (using the PDCA cycle, Plan-Do-Check-Act) required to developthe proposed work. Study types used are descriptive and exploratory, which look for the necessary information collection through observation, questionnaires and reports, and taking as the basis, the official and confidential document prepared by the WBO. The research method is deductive, as it is part of the standard BASC and from there you start to analyze and evaluate its concrete application in the organization. To conclude, it is stated that the company is on track. During this time, the company has advanced the necessary adjustments to achieve certification in the standard mentioned above, although there are still some aspects to check and improve. This analysis was of great help to form the basis to continue the implementation process, which has not been completed because of the complexity and thoroughness in meeting its requirements.